Factors related to parental COVID-19 vaccine hesitancy for children: An exploratory factor analysis model - Reenaa Mohan; R Sindhuri; Kanimozhi Thandapani; D.S Karthika Devi; Kalaiselvan Ganapathy (Journal of Family Medicine and Primary Care)
Introduction: This pandemic has been accompanied by an overabundance of information and misinformation, an ‘infodemic’ on a global scale which have made acceptability of COVID-19 vaccine a major challenge. The objective of the study was to find out the Beliefs of mothers towards COVID-19 vaccine for children and its impact on vaccine hesitancy. Materials and Methods: After obtaining Institutional ethical clearance and informed consent, a total of 360 mothers who were having at least one child from 5 to 18 years were recruited based on simple random sampling. Face-to-face interview was conducted. The questionnaire was based on the WHO-SAGE working group on vaccine hesitancy. Based on Bartlett’s test of sphericity, the model was found to be fit (there is adequate number of correlations for factor analysis) and KMO test results imply the samples are adequate for factor analysis. K means cluster analysis was used to divide the samples into three clusters and individual respondent’s cluster membership was also identified. Results: It was found 49.4% of mothers were hesitant to vaccine their children against COVID-19. The seven items (reasons for vaccine hesitancy) were grouped into three dimensions (believes in vaccine effectiveness but concerned about side effects, believes in the importance of taking COVID vaccine, trusts information about COVID vaccine), based on how each item loads on to each of three factors. Cluster 1 was that they believe in effectiveness of vaccine but are concerned about side effects (.92094). Conclusion: Mothers’ concerns were mainly about the safety and adverse effects of vaccine.